Behaviouristic Model of the Main Character Speech Behaviour in Split Movie Script - Vindy Yulandari Mustapa; Dahlia D. Moelier; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
The research aims to analyze the speech behavior of the main character, Kevin, who has a psychological issue, namely Dissociative Identity Disorder (DID) in Split movie script, which causes Kevin to have several different characters in one body. The data analyze the process of forming and trigger factors in speech behaviour in the Split movie script using qualitative descriptive method with B.F Skinner’s theory. The result shows there are two process of forming behavior namely classical conditioning, each of them has its own purpose in taking the main personality based on their will and operant conditioning process of each character that appears to takes control of the main personality because of the response from someone who makes them have to take control that emerges through this process is due to response given by others. The trigger factor in speech behaviour based on three process namely natural selection, each character taking control of the main personality due to their own desires, cultural control triggered each one of them to takes control through the main personality that control from people around and internal condition takes control due to encouragement by someone who makes them feel fear, anger and anxiety.